CRESST-II: dark matter search with scintillating absorbers; Nuclear Physics B- Proceedings Supplements; Vol. 138 - Angloher G.; Bucci C.; Cozzini C.; Feilitzsch F. von; Frank T.; Hauff D.; Henry S.; Jagemann Th.; Jochum J.; Kraus H.; Majorovits B.; Ninkovic J.; et al. (2005, 2005)
Title screen